Factors Affecting Consumer Attitudes and Intentions on the Intention to Buy Products through Retail Brand Pages on Social Media: Office Workers in Indonesia - Yusup Setiawan; Edi Hamdi (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The development of social media as a means of selling and the high number of social media users make consumer-brand engagement behavior on social media, especially Facebook, need to be studied more deeply. In line with this, this study aims to study 5 antecedents of attitudes towards consumers' intentions to engage with retail brands through social media which ultimately affect the intention to buy products, and 1 antecedent of moderation on attitudes towards product purchase intentions. The study was conducted on office workers in Indonesia with a quantitative survey method on 195 respondents. The analytical method used is Structural Equation Model I (SEM). This study found that consumer attitudes towards engagement with retail brands through Facebook were influenced by enjoyment, peer communication, and credibility, while attitudes had a strong influence on intentions to engage with retail brands through Facebook and subsequently strongly associated with intention to purchase through that Facebook page. This supports previous research. The first new things found were that consumer attitudes had a positive effect on consumers' purchase intentions and the second was that expectations of confirmation moderated attitudes toward purchase intentions through retail brand Facebook pages. The managerial contribution of this research helps retailers understand how to attract consumers to engage with retail brands on Facebook.